Collision frequency and free length path of electrons of semiclassical dense plasma - Turekhanova, K.M.; Kaliyeva, D.S. (Хабаршы. Физика сериясы, 2018)
Nowadays the study of collision processes of dense semiclassical plasma is of considerable interest in many experimental facilities. The paper studies the collision processes of dense semiclassical plasma taking into account the quantum mechanical effects of diffraction and symmetry at small distances and the effects of screening of charge’s field at large distances. The collision characteristics of dense semiclassical plasma are obtained numerically such as the dependences of the electron collision frequency on the parameter of nonideality and the free length path of electrons on the parameter of nonideality are determined. It has shown that taking into account the screening effect and quantum-mechanical effects of diffraction and symmetry in dense semiclassical plasma leads to a maximum on the electron collision frequency’s curve at certain values of the nonideality parameter. The free length path of electrons has a minimum in some values of the nonideality parameter.